Influence of attitudinal traits on academic engagements of senior secondary islamic studies students in Irepodun, Osun State - Owoyale-Abdulganiy, Ibrahim Solahudeen; Jamiu, Abdus-Samiu Ola; Usman, Abubakar Yahaya (Papanda Publisher, 2025)
This study investigated the influence of attitudinal traits on academic engagements of senior secondary Islamic Studies Students in Irepodun, Osun State. The objectives of the study were to investigate prevalent attitudinal traits, positive attitudinal traits, impact of negative attitudinal traits and intervention to enhance positive attitudinal traits and senior secondary Islamic Studies students’ academic engagements. Descriptive survey research method was adopted for the study. The population for the study consisted of all 185 Islamic studies students in the 20 secondary schools in Osun State. A sample of 185 respondents was selected from the population using a simple random sampling technique. A questionnaire titled “Attitudinal Traits and Academic Engagements of Senior Secondary Islamic Studies Students Questionnaire (ATAESSISSQ). The reliability of instrument was established with the use of test-re-test methods and value of 0.78 was obtained. Four research questions were answered. The study found that positive attitudinal traits such as enthusiasm, resilience, and open-mindedness play a significant role in fostering academic engagement among senior secondary students of Islamic Studies in Irepodun, Osun State. Negative traits, such as apathy, pessimism, and low self-efficacy, were found to hinder academic engagements. Interventions aimed at promoting resilience, enhancing motivation, providing peer support, and incorporating mindfulness practices could significantly improve students' attitudes and academic engagement in Islamic Studies. Based on these findings, it was recommended among others that teachers should adopt interactive and student-centered teaching methods that make Islamic Studies more engaging, such as group discussions, debates, and real-world applications of Islamic teachings. Teachers should create an inclusive learning environment that encourages students to explore different perspectives and ideas, fostering a more open and adaptable mind-set in their approach to Islamic Studies.